Understanding and Interpreting Laser Diagnostics in Flames: A Review of Experimental Measurement Techniques - Evans, Michael J.; Medwell, Paul R. (Frontiers in Mechanical Engineering, 2019)
There is a wealth of existing experimental data of flames collected using laser diagnostics. The primary objective of this review is to provide context and guidance in interpreting these laser diagnostic data. This educational piece is intended to benefit those new to laser diagnostics or with specialisation in other facets of combustion science, such as computational modelling. This review focuses on laser-diagnostics in the context of the commonly used canonical jet-in-hot-coflow (JHC) burner, although the content is applicable to a wide variety of configurations including, but not restricted to, simple jet, bluff body, swirling and stratified flames. The JHC burner configuration has been used for fundamental studies of moderate or intense low oxygen dilution (MILD) combustion, autoignition and flame stabilisation in hot environments. These environments emulate sequential combustion or exhaust gas recirculation. The JHC configuration has been applied in several burners for parametric studies of MILD combustion, flame reaction zone structure, behaviour of fuels covering a significant range of chemical complexity, and the collection of data for numerical model validation. Studies of unconfined JHC burners using gaseous fuels have employed point-based Rayleigh-Raman or two-dimensional Rayleigh scattering measurements for the temperature field. While the former also provides simultaneous measurements of major species concentrations, the latter has often been used in conjunction with planar laser-induced fluorescence (PLIF) to simultaneously provide quantitative or qualitative measurements of radical and intermediary species. These established scattering-based thermography techniques are not, however, effective in droplet or particle laden flows, or in confined burners with significant background scattering. Techniques including coherent anti-Stokes Raman scattering (CARS) and non-linear excitation regime two-line atomic fluorescence (NTLAF) have, however, been successfully demonstrated in both sooting and spray flames. This review gives an overview of diagnostics techniques undertaken in canonical burners, with the intention of providing an introduction to laser-based measurements in combustion. The efficacy, applicability and accuracy of the experimental techniques are also discussed, with examples from studies of flames in JHC burners. Finally, current and future directions for studies of flames using the JHC configuration including spray flames and studies and elevated pressures are summarised.